Evaluation of the best environment for the six-minute walk test - Newton Santos de Faria Júnior; Cláudio Hiroshi Nakata; Luís Vicente Franco de Oliveira; Gaspar Rogério Chiappa; Gerson Cipriano Júnior
AbstractIntroduction The purpose of the six-minute walk test (6MWT) is to evaluate cardiopulmonary capacity using a low-cost test that is easy to administer, generally well tolerated by different populations and reflects one's performance on activities of daily living. However, few studies have been conducted to determine the difference between performing the 6MWT indoors and outdoors.Objective The aim of the present study was to compare the distance covered on the 6MWT performed indoors and outdoors and evaluate the following physiological variables: heart rate, blood pressure and the subjective sensation of shortness of breath, using the Borg perceived exertion scale.Materials and methods A prospective, randomized, clinical trial was conducted involving eight healthy females not engaged in regular physical activity, with mean age 23.75 ± 1.67 years. Each subject performed the 6MWT indoors and outdoors with a 30-minute interval between tests. The order of the tests was determined randomly.Results The mean distance traveled was 578 ± 50.07 m on the outdoor trial and 579.95 ± 45.35 m on the indoor trial (p = 0.932). The mean physiological variables were 82.25 ± 11.02 bpm (indoors) versus 84.38 ± 9.42 bpm (outdoors) for heart rate, 121.88 ± 10.28 mmHg (indoors)versus 118.75 ± 19.40 mmHg (outdoors) for systolic blood pressure, 81.88 ± 9.74 mmHg (indoors) versus 80.50 ± 7.89 mmHg (outdoors) for diastolic blood pressure and a mean score of 12 on the perceived exertion score in both environments.Conclusions The present data demonstrate no differences in the distance walked on the 6MWT or the physiologic variables of participants between the indoor and outdoor trials.